Heeding the Song Unseen - Bell, Anne (UnderCurrents: Journal of Critical Environmental Studies, 1993)
If one descends the Tatshenshini River* in July, one is bound to come across the .hermit thrush hopping about under the poplar, willow and scrubby spruce. A reclusive bird, its name seems to suit its unassuming appearance and the sparse, rugged surroundings in which I first heard it sing.. Like a small brown robin deprived of its orange breast, it could easily pass unnoticed, and I myself would scarcely have paid it much attention had it not been for its song, a splash of delicate, resonant crystal and sparkling cascades. [...]